2019
DOI: 10.1007/s13311-018-0660-1
|View full text |Cite
|
Sign up to set email alerts
|

Brain Machine Interfaces for Vision Restoration: The Current State of Cortical Visual Prosthetics

Abstract: Loss of vision alters the day to day life of blind individuals and may impose a significant burden on their family and the economy. Cortical visual prosthetics have been shown to have the potential of restoring a useful degree of vision via stimulation of primary visual cortex. Due to current advances in electrode design and wireless power and data transmission, development of these prosthetics has gained momentum in the past few years and multiple sites around the world are currently developing and testing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 101 publications
0
58
0
2
Order By: Relevance
“…A preliminary study in one blind patient demonstrated the safety and basic functional aspects of the device. Ongoing clinical trials that started in late 2017 have so far included five blind patients with a follow-up planned for 5 years ( Niketeghad and Pouratian, 2019 ). Preliminary results indicated that patients were able to perceive phosphenes ( Barry et al, 2020 ).…”
Section: Brain Interfaces For Vision Recoverymentioning
confidence: 99%
“…A preliminary study in one blind patient demonstrated the safety and basic functional aspects of the device. Ongoing clinical trials that started in late 2017 have so far included five blind patients with a follow-up planned for 5 years ( Niketeghad and Pouratian, 2019 ). Preliminary results indicated that patients were able to perceive phosphenes ( Barry et al, 2020 ).…”
Section: Brain Interfaces For Vision Recoverymentioning
confidence: 99%
“…[59,60] The purpose of these devices is to restore function to different organs in our body that suffered from neuronal damage whether due to an injury, disease or a physiological condition (Figure 8). Success of these devices is great and reports are increasing for more and more advanced devices that restore close to full activity of vision, [61] hearing, [62] and limbs functionality. [63] Conclusions and a Glimpse to the Future…”
Section: Interfacing With Organs and Specific Tissuesmentioning
confidence: 99%
“…Focusing on pediatrics, Ibrahim and colleagues [17] address neuromodulatory strategies for the treatment of intractable epilepsy in children, including putative mechanisms of action and biomarkers for treatment success. Addressing vision restoration, Niketeghad and Pouratian [18] describe the historical thinking on cortical visual prosthetics, as well as the current state of the art, explaining the design of current devices that are either under development or in the clinical testing phase. Rabbani and colleagues [19] then complete this section by introducing us to the field of neural speech decoding using electrocorticography, exploring what a brain-computer interface for speech might entail.…”
Section: Brain-computer Interfaces For Restoring Movement Seizure Comentioning
confidence: 99%